Gaze and Mouse Coordination in Everyday Work - Liebling, Dan; Dumais, Susan (4th International Conference on Pervasive Eye Tracking and Mobile Eye-Based Interaction, 2014)
Gaze tracking technology is increasingly common in desktop, laptop and mobile scenarios. Most previous research on eye gaze patterns during human-computer interaction has been confined to controlled laboratory studies. In this paper we present an in situ study of gaze and mouse coordination as participants went about their normal activities. We analyze the coordination between gaze and mouse, showing that gaze often leads the mouse, but not as much as previously reported, and in ways that depend on the type of target. Characterizing the relationship between the eyes and mouse in realistic multi-task settings highlights some new challenges we face in designing robust gaze-enhanced interaction techniques.